2018
DOI: 10.1103/physrevd.97.114002
|View full text |Cite
|
Sign up to set email alerts
|

Form factors of the d*(2380) resonance

Abstract: In order to explore the possible physical quantities for judging different structures of the newly observed resonance d à ð2380Þ, we study its electromagnetic form factors. In addition to the electric charge monopole C0, we calculate its electric quadrupole E2, magnetic dipole M1, and magnetic octupole M3 form factors on the base of the realistic coupled ΔΔ þ C 8 C 8 channel dà wave function with both the S-and D-partial waves. The results show that the magnetic dipole moment and electric quadrupole deformatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…(2) The D-wave is ignored in the calculations for the strong decay and charge distribution, because it is negligibly small. However, it may contribute to the higher multi-pole form factors, such as E2, and M 3 since those values are closely related to the matrix elements of the high-rank operators [26]. The more detailed information about the wave function of d * is referred to Ref.…”
Section: Structure and Wave Function Of D * (2380) In The Extendementioning
confidence: 99%
See 1 more Smart Citation
“…(2) The D-wave is ignored in the calculations for the strong decay and charge distribution, because it is negligibly small. However, it may contribute to the higher multi-pole form factors, such as E2, and M 3 since those values are closely related to the matrix elements of the high-rank operators [26]. The more detailed information about the wave function of d * is referred to Ref.…”
Section: Structure and Wave Function Of D * (2380) In The Extendementioning
confidence: 99%
“…Consequently, the electromagnetic form factors of a the higher spin particle are also a discriminating quantity for different approaches. In particular, for the d * state, if there is a considerably large hidden-color component (HCC) in it, we have found that, although such a component does not contribute to its hadronic strong decay in the leading-order calculation, it plays a rather important role in the charge distribution calculation [13][14][15]25], and the obtained charge distribution with a compact 6-quark scenario is quite different from that having a D 12 π (or ∆πN ) structure [25,26]. Other physical quantities, like the d * production in the e + e − annihilation, and constituent quark counting rule in the high energies may also provide some other information for its structure [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In order to manifest the C 8 C 8 effect, we apply the electromagnetic (EM) probes to d * (2380). Since it is a spin-3 particle, it has all together 7 form factors [18,19]. We calculate its EM form factors (see Fig.…”
Section: Decays Of D * (2380) In Our Approachmentioning
confidence: 99%
“…Currently, two scenarios were proposed for the structure of d * (2380). One assumes that it has a compact structure, and may be an exotic hexaquark dominated state [11][12][13][14][15][16][17][18][19][20]. Another basically regards it as a D 12 π molecular-like hadronic state, which originates from a three-body ∆Nπ resonance assumption [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The news from experimentalists spread around quickly and kindled the enthusiasm in theorists in a moment. Many hypotheses were proposed and various methods were employed to uncover the property of this particle [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, up to now, d à ð2380Þ has only shown up in the nuclear reaction process.…”
Section: Introductionmentioning
confidence: 99%